Sprouting Value Index: A Research Perspective in Artificial Vegetative Propagation in Tree Species - Justin R. Nayagam (Research Perspective on Biological Science Vol. 1, 2025)
The rooting potential of Saraca asoca stem cuttings was evaluated using three concentrations of Indole-3-butyric acid (IBA): 300 ppm, 500 ppm, and 1000 ppm. The study analyzed the obtained data using the Sprouting Value Index (SVI) method to assess rooting vigor, sprouting efficiency and the most suitable rooting medium. Field experiments were conducted over three years at four-month intervals in Central Kerala, Peninsular India, using three different rooting media. Control cuttings did not exhibit rooting. The results demonstrated the highest SVI when prop root cuttings were planted in root trainers with coir pith compost (RTCP) across all IBA concentrations. IBA treatment significantly increased sprouting percentage while reducing the time required for sprouting and rooting initiation. However, elevated Cuttings Without Rooting (CWR) and Shoot-Up Percentage (SUP) values suggest possible issues related to management practices, dormancy, or cultivar genotype.